NRG1/ErbB signalling controls the dialogue between macrophages and neural crest-derived cells during zebrafish fin regeneration - Béryl Laplace-Builhé (Nature Portfolio, 2021)
Some fish can regenerate appendages by formation of a structure called the blastema. Here, the authors use single-cell RNA sequencing to characterize the cells required for blastema formation and fin regeneration and identified neural crest cells that orchestrate regeneration via the NRG1/ErbB axis